PENGARUH PUPUK KANDANG AYAM DAN NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) KULTIVAR SUMENEP - Rusmana, Rusmana; Jaenudin, Amran; Budirokhman, Dodi (Agroswagati : Jurnal Agronomi, 2024)
This research aims to determine the effect of chicken manure and NPK on the growth and yield of shallot plants (Allium Ascalonicum L.) Sumenep cultivar. The research was carried out in Lengkong Village, Garawangi District, Kuningan Regency, in November – February 2024. The research method used was a randomized block design (RAK) with a paktorial pattern. The treatment consisted of two factors which were repeated three times. The first factor is chicken manure which consists of four levels, namely 0 tons/ha, 5 tons/ha, 10 tons/ha and 15 tons/ha, while the second factor is the dose of NPK fertilizer which consists of three levels, namely 50 kg/ha. , 75 kg/ha, and 100 kg/ha. The results of the research showed that the Chicken Manure and NPK treatments did not provide a real interaction with all treatments, but had an independent influence from 100 kg/ha NPK fertilizer on plant height at 28 DAT and 35 DAS, number of leaves at 28 DAS and 35 DAS, there was also an effect independently from the treatment of 10 tonnes/ha of chicken manure on tuber diameter. Treatment with a dose of chicken manure at a dose of 15 tons/ha gave the best results in dry tuber weight per plot, namely 1.68 kg/plot, equivalent to 6.22 tons/ha and an NPK dose of 100 kg/ha gave the highest results in dry tuber weight per plot. plot, namely 1.65 kg, equivalent to 6.11 tonnes/ha.